المنهج النبوي في تحقيق التوافق الأسري - جمعة عثماني; عبير حسني; نصيرة عبد المالك (university of eloud, 2021)
تقدم هذه الدراسة موضوعا مهما متمثلا في المنهج النبوي ودوره في تحقيق التوافق الأسري ، والذي له أهمية بالغة في تدعيم البنى الدفاعية الأساسية في الإسلام والتي من أهمها الأسرة ، فتهدف إلى بيان أهم الأساليب الواجب اتخاذها لتحقيق الأمن بين الزوجين والأبناء ، والتعرف على معنى التوافق وأنواعه ومجالاته وأساليبه المستنبطة من المنهج النبوي،مستخدمة في ذلك المنهج الوصفي والتحليلي والاستقرائي ،فخلصت الدراسة إلى أن المنهج النبوي منهج يساعد الأسرة على الاستقرار والانسجام والتوافق، وأنه لا يتحقق إلا بتوفر أسلوب الرحمة والمودة والإحسان والرفق والمداعبة ..،ويبقى الاقتداء بالهدي النبوي الحل الأمثل لخلاص الأسر الإسلامية اليوم من مشكلاتها بما فيها التفكك والانهيار وخروجها من آثار الجاهلية إلى الحياة الإسلامية. This study presents an important topic represented in the Prophetic approach and its role in achieving family harmony, which is of great importance in strengthening the basic defensive structures in Islam, the most important of which is the family. And his methods deduced from the prophetic method, using the descriptive, analytical and inductive method, The study concluded that the Prophetic approach is a method that helps the family to stability, harmony and harmony, and that it can only be achieved by the availability of the method of mercy, affection, charity, kindness and foreplay.. and following the prophetic guidance remains the best solution for the salvation of Islamic families today from their problems, including disintegration and collapse and their exit from the effects of ignorance to life. Islamic.
Keywords: التوافق الأسرة الرحمة المنهج الإحسان المداعبة Compatibility family compassion curriculum.Charity foreplay